Awareness and practices of parents about immunization of children in the age group 2-5 years - Upadhye, Jayant V.; Marathe, Sanjay M.; Mandlik, Milind R.; Upadhye, Aditi J.; Upadhye, Jayshree J. (International Journal of Contemporary Pediatrics, 2018)
Background: Immunization is a highly cost-effective way of reducing morbidity and mortality in children in developing countries Objectives of this study were to determine awareness of parents and immunization status of children in the age group of 2 to 5 years and study the social factors influencing immunization status of a child. Methods: A total 200 children aged 2-5 years who are attending Pediatric OPD, immunization clinic from May 2017 to April 2018 were enrolled in the present study. Results: In the present study, 170 children (85%) received full immunization given by Government of India free of cost while 30 children (15%) got partial immunization. 90 children (45%) received full immunization while 110 children (55%) got partial immunization NOT given by Government of India free of cost. Parents of 80 children (40%) were unaware of vaccination schedule, parents of 70 children (35%) did not give full vaccination due to high cost, parents of 30 children (15%) had wrong beliefs while parents of 20 children (10%) couldn’t understand the importance of vaccination due to less education. Conclusions: The goal of 85% coverage is an uphill task. Adverse effects following immunization, busy parents, lack of knowledge seems to be a major contributing factor for the non-success of this national program. Parent’s occupation and education are statistically significant contributing factors for the poor immunization coverage among these children.